Live Synchronous Web Meetings in Asynchronous Online Courses: Reconceptualizing Virtual Office Hours - Lowenthal, Patrick R.; Dunlap, Joanna C; Snelson, Chareen (Online Learning, 2017)
Most online courses rely solely on asynchronous text-based online communication. This type of communication can foster anytime, anywhere reflection, critical thinking, and deep learning. However, it can also frustrate participants because of the lack of spontaneity and visual cues and the time it takes for conversations to develop and feedback to be shared, as well as the self-directedness and discipline it requires of participants to regularly check in and monitor discussions over time. Synchronous forms of communication can address some of these constraints. However, online educators often avoid using synchronous forms of communication in their courses, because of its own constraints. In this paper, we describe how we integrated live synchronous web meetings into asynchronous online courses, collected student feedback, and made iterative changes and refinements based on student feedback over time. We conclude with implications for practice.